1987
DOI: 10.1093/annhyg/31.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Benzene at Different Work Places in Sweden

Abstract: The exposure to benzene at different work places in Sweden where petrol is produced or handled has been investigated. The high benzene content (max 5 %, v/v) in Swedish petrol means that many workers are exposed to benzene vapours during their working day. The measurements showed that the exposure of most workers was below the Swedish occupational standard value (8 h TWA, 16 mg m −3). Short-time sampling showed the occurrence of exposures to high concentrations above the occupational standard value for 15 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Two samples exceeded the project-specific guideline limit for benzene (300 µg/m 3 ). Elsewhere, much higher benzene exposures have been reported in other studies from Europe and the USA, especially in the past (Bates et al 1994 ; Burns et al 2016 ; Capleton and Levy 2005 ; Claydon et al 2000 ; Coker et al 1987 ; Gaffney et al 2010 , 2011 Kreider et al 2010 ; Nordlinder and Ramnas 1987 ; Panko et al 2009 ; Verma et al 2001 ), with AM exposures in the range of a few hundred to thousands of µg/m 3 . The majority of the samples were below 1 ppm (about 3200 µg/m 3 ), which is the OEL value applied in several countries (Capleton and Levy 2005 ; Health Council of the Netherlands 2014 ).…”
Section: Discussionmentioning
confidence: 84%
“…Two samples exceeded the project-specific guideline limit for benzene (300 µg/m 3 ). Elsewhere, much higher benzene exposures have been reported in other studies from Europe and the USA, especially in the past (Bates et al 1994 ; Burns et al 2016 ; Capleton and Levy 2005 ; Claydon et al 2000 ; Coker et al 1987 ; Gaffney et al 2010 , 2011 Kreider et al 2010 ; Nordlinder and Ramnas 1987 ; Panko et al 2009 ; Verma et al 2001 ), with AM exposures in the range of a few hundred to thousands of µg/m 3 . The majority of the samples were below 1 ppm (about 3200 µg/m 3 ), which is the OEL value applied in several countries (Capleton and Levy 2005 ; Health Council of the Netherlands 2014 ).…”
Section: Discussionmentioning
confidence: 84%
“…Figure 4 shows the mean benzene concentrations for each dataset identified from these studies that used averaging times of ≥3 hours, along with maximum detected values when reported. More details regarding these and other relevant studies from the literature (10,(38)(39)(40)(41)(42)(43) figure 4 also shows the mean and maximum non-task airborne benzene concentrations for Baton Rouge dock workers from this study based on samples collected before 1990 (0.28 and 6.3 ppm, respectively) and for samples collected during 1990 and later years (0.15 and 15.3 ppm, respectively). The mean airborne benzene concentration for dock workers from this study based on non-task samples (0.28 ppm) lies within the range of means from the published studies, and below 82% of the mean concentrations reported from the studies depicted in figure 4, despite the fact that the Baton Rouge data set was targeted to over-represent benzene handling activities as discussed elsewhere (4).…”
Section: Task Exposure Estimatesmentioning
confidence: 95%
“…It is a confirmed human carcinogen [ 4 ] and epidemiological studies have shown it causes the occurrence of acute and chronic leukemia, even at low concentrations [ 5 ]. Acute exposure to high benzene concentrations can also affect the central nervous system and cause dizziness, headaches and nausea, while chronic exposure can give rise to more serious adverse health effects such as blood disease, haematotoxicity, genotoxicity, increased levels of persistent chromosome aberrations, reproductive effects and mortality [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%